International Legal Framework Regarding Human Trafficking - Airapetean, Artur; Corsei, Andreea (Acta Universitatis Danubius. Juridica, 2022)
International failures in this field have several causes. Thus, many states have preferred to include the crime of human trafficking in their own criminal codes, without considering it necessary to regulate it through a special law. That could favor the legislation of all aspects of the crime itself, of those related to it, of the particular aspects of a procedural nature, including those regarding international cooperation in the matter. Another cause could be that of criminalizing only human trafficking for the purpose of prostitution, without taking into account the other forms. In addition, most of the laws of the world's states did not apply a special treatment to the victims of human trafficking, offering them the necessary protection and assistance, but on the contrary, the victims were accused of prostitution, of illegal border crossing, of falsifying travel documents, being expelled and repatriated in their country of origin.